Pengaruh Return On Asset, Earning Per Share, dan Debt Ratio Terhadap Harga Saham Pada Perusahaan Indeks LQ-45 di Bursa Efek Indonesia - Mahadewi, I Gusti Agung Ayu Bintang; Candraningrat, Ica Rika (E-Jurnal Manajemen; Vol 3 No 12 (2014), 2014)
The purpose of this study was to determine the effect of Return on Assets ( ROA), Earning Per Share (EPS), and Debt Ratio (DR) towards the stock price on the LQ-45 index company in Indonesia Stock Exchange (IDX) 2011-2013. This study used a non-participant  observation method by analyzing financial statements published on the official website of the Stock Exchange ( www.idx.co.id ). The sample was 25 companies which are taken by purposive sampling method. The data analysis technique used is multiple linear regression. The results of this study indicate that ROA and EPS partially positive and significant impact on stock prices, while the DR and has in significant negative effect on the LQ-45 index company on the Indonesia Stock Exchange 2011-2013.
Keywords: return on asset, earning per share, debt ratio, harga saham